Engaging, Explicit, and Elaborated: An Initial Trial of Media-Enhanced Preschool Vocabulary Instruction. Issue 4 (October 2022) - Phillips, Beth M.; Oliver, Felesa; Willis, Karli B.
Abstract : Children from backgrounds of poverty often lag behind more advantaged peers in early language skills, including breadth and depth of vocabulary knowledge. We report the results of a pilot study of an explicit and elaborated vocabulary intervention in preschool classrooms serving children from lower-income backgrounds. The intervention used multimodal instruction, including segments from public television children's programs and interactive games, to build children's knowledge of and semantic connections for 128 words across 18 weeks of daily lessons. Within 39 classrooms representing childcare, Head Start, and public prekindergarten settings, 192 preschool-age children ( M = 52.10 months) participated in structured lessons and extension activities delivered by teachers and aides. Within-child comparisons of growth for taught target words versus matched untaught words revealed that children grew on all words but demonstrated significantly greater growth for taught words. Results support the value of elaborated and explicit vocabulary instruction and the role of visual media as contexts for preschooler's word learning.